Serosurveillance after a COVID‐19 vaccine campaign in a Swiss police cohort. Issue 7 (6th June 2022) - Sendi, Parham; Thierstein, Marc; Widmer, Nadja; Babongo Bosombo, Flora; Büchi, Annina Elisabeth; Güntensperger, Dominik; Blum, Manuel Raphael; Baldan, Rossella; Tinguely, Caroline; Gahl, Brigitta; Heg, Dik; Theel, Elitza S.; et al.
Abstract: Introduction: To assess the risk for COVID‐19 of police officers, we are studying the seroprevalence in a cohort. The baseline cross‐sectional investigation was performed before a vaccination campaign in January/February 2021, and demonstrated a seroprevalence of 12.9%. Here, we demonstrate serosurveillance results after a vaccination campaign. Methods: The cohort consists of 1022 study participants. The 3‐ and 6‐month follow‐up visits were performed in April/May and September 2021. Data on infection and vaccination rates were obtained via measuring antibodies to the nucleocapsid protein and spike protein and online questionnaires. Results: The mean age of the population was 41 ( SD 8.8) years, 72% were male and 76% had no comorbidity. Seroconversion was identified in 1.05% of the study population at the 3‐month visit and in 0.73% at the 6‐month visit, resulting in an infection rate of 1.8% over a time period of 6 months. In comparison, the infection rate in the general population over the same time period was higher (3.18%, p = .018). At the 6‐month visit, 77.8% of participants reported being vaccinated once and 70.5% twice; 81% had an anti‐S antibody titer of >250 U/ml and 87.1% of ≥2 U/ml. No significant association between infection and job role within the department, working region, or years of experience in the job was found. Anti‐spike antibody titers of vaccinated study participants showed a calculated decreasing trend 150–200 days after the second vaccine dose. Conclusion: These data confirm the value of the vaccination campaign in an exposed group other than healthcare professionals. Graphical abstract: In this serosurveillance study, we observed a high vaccination and low infection rate during the delta surge in a police cohort. Anti‐Spike antibody titers of vaccinated study participants showed a calculated decreasing trend 150–200 days after the second vaccine dose.